Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.1209
|View full text |Cite
|
Sign up to set email alerts
|

SAT0222 Clinical risk stratification for hydroxychloroquine prescribing in a large urban district general hospital

Abstract: Background:New 2017 British Society of Rheumatology guidelines have recommended baseline formal ophthalmic examination, ideally including objective retinal assessment for example using optical coherence tomography, within 1 year of commencing an antimalarial drug. While the feasibility and costing of this recommendation is being assessed, we audited the current risk assessment for hydroxychloroquine prescriptions (HCQ) against the American College of Ophthalmology (ACO) guidelines for HCQ published in 2016. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…17 Another study also revealed that half of the patients had weight documented before prescription but not used to determine the doses. 18 Further, a safe dose of 5mg/kg real bodyweight places short, obese patients at unnecessarily increased risk for retinopathy. 20 It is also not uncommon that patients may develop renal disease or experience weight loss (and a higher dose) after 1 year and these patients will probably not realize they are high risk and will go without follow-up for 4 more years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Another study also revealed that half of the patients had weight documented before prescription but not used to determine the doses. 18 Further, a safe dose of 5mg/kg real bodyweight places short, obese patients at unnecessarily increased risk for retinopathy. 20 It is also not uncommon that patients may develop renal disease or experience weight loss (and a higher dose) after 1 year and these patients will probably not realize they are high risk and will go without follow-up for 4 more years.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, all the patients having good visual acuity and vision remain unchanged for the period of this study except the 3 patients with 6/12 visual acuity who improved with glasses prescription and/or artificial tears. RCOphth, 1993 14 RCOphth, 1998 15 AAO, 2002 16 RCOphth, 2004 17 RCOphth, 2009 18 AAO, 2011 19 AAO, 2017 20 RCOphth, 2018 21 Recommended dosage 6.5 mg/kg lean weight 6.5 mg/kg lean weight 6.5 mg/kg lean weight 6.5 mg/kg lean weight 6.5 mg/kg lean weight 6.5 mg/kg lean weight 5.0 mg/kg real weight Comparing the central macular thickness and optic disc retinal nerve fiber layer thickness (RNFL) using Cirrus SD-OCT in patients with connective tissue diseases on hydroxychloroquine pre-treatment, 3 months, and 6 months post-treatment.…”
Section: Demographic Datamentioning
confidence: 99%